Characteristics of central vein stenosis patients at Abdoel Wahab Sjahranie Hospital Samarinda - Fritzky Wandy Thedjakusuma; Ramadhani Hengki Wijaya; David Hermawan Christian; Michael Caesario; Ivan Joalsen Mangara Tua (Journal of Indonesia Vascular Access, 2023)
Background: Central vein stenosis (CVS) is a common complication in using a central venous catheter in hemodialysis (HD) access, and its incidence in Indonesia has not been obtained. This study aims to evaluate the characteristics of CVS patients in Abdul Wahab Sjahranie Hospital, Samarinda. Methods: This cross-sectional descriptive study was conducted by collecting CVS patients’ data from the medical records between January 2018 to August 2021. The demographic data and the characteristics of CVS patients were collected. The data obtained were analyzed in descriptive form and displayed in a table. Results: This study involved 23 subjects. The characteristics of CVS patients included: Highest sex group was males (61%); Age group was in the range 51-70 years (60%); Clinical feature was swelling (83%); Site of stenosis was in the subclavian vein (87%), on the left side (57%), type of occlusion were partial (67%) and single (87%), and the result of angioplasty was a success (61%). Conclusion: This study showed that CVS was male predominant, in the range 51-70 years, the most complaint was swelling in the arms that were mostly on the left side, and the location of the most stenosis was in the subclavian vein, with partial and single occlusion, as well as good treatment with angioplasty.